Theoretical modelling and experimental identification of nonlinear torsional behaviour in harmonic drives - Tjahjowidodo, Tegoeh. (2013)
The demand for accurate and reliable positioning in industrial applications, especially in robotics and high-precusion machines, has led to the increased use of harmonic drives. The unique performance features of harmonic drives, such as high reduction ratio and high torque capacity in a compact geometry, justify their widespread application. However, nonlinear torsional compliance and friction are the most fundamental problems in these components, manifesting themselves as a combination of stiffening spring together with hysteresis at reversal points. Accurate modelling of the static and dynamic behaviour is expected to improve the performance of the system. This paper offers a model for torsional compliance of harmonic drives. A statistical measure of variation is defined, by which the reliability of the estimated parameters for different operating conditions, as well as the accuracy and integrity of the proposed model, are quantified. The model performance is assessed by simulation to verify the experimental results. Two test setups have been developed and built, which are employed to evaluate experimentally the behaviour of the system. Each setup comprises a different type of harmonic drive, namely the high load torque and the low load torque harmonic drive. The results show an accurate match between the simulation torque obtained from the identified model and the measured torque from the experiment, which indicates the reliability of the proposed model.